A systematic approach to the sports scheduling problem for the Turkish professional football league - Isik, Eyup Ensar; Akyol, Sebnem Demirkol; Baykasoglu, Adil (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Scheduling of sports competitions has become an area of interest for researchers with the globalization of sports and its spread to large crowds. Round Robin tournament derivatives are generally applied among different types of tournaments, especially in leagues. This study aims to create schedules for the Turkish Professional Football League. Indicators such as the number of breaks, weighted carry-over effect, and specific requirements are considered as characteristic values reflecting the league's quality. In this study, an integer programming (IP) model is developed to solve the scheduling problem, and it is observed that the IP model gives the optimum schedule for small-sized problems only. As a remedy, a two-phase heuristic solution procedure is proposed. The heuristic procedure first finds a pattern set and then constitutes the schedule. Different pattern sets and schedules are presented in the experimental results. The results show that the proposed heuristic method obtains the best schedules concerning the current schedule and the proposed IP models for various problem characteristics.
Keywords: Heuristics; Integer programming; Round robin tournament; Sports scheduling; SOCCER LEAGUE; ALGORITHM; GAMES; Computer Science; Engineering